International experience of compensation of damage caused to the consumer through contracts concluded on the Internet (Eurasian Research Bulletin, 2023)
As current directions in the field of consumer rights protection, today in many developed countries of the world, sales of goods on the basis of distant contracts, services provided to consumers through the Internet, and new types of relations with the participation of consumers through electronic trading platforms are emerging, in turn, determining the legal basis of these relations and the counterparty of consumers special attention is paid to the research of clarification issues. The primary tasks are to ensure the rights of the consumer, to determine the size and amount of the damage caused to him, and to make it possible for him to fully realize his rights established by the law